In silico annotation of the genes involved in biosynthesis of lipopolysaccharide for Burkholderia pseudomallei. - Lai, L. Suang; Sekawi, Zamberi; Abdullah Al-Haj, Nagi Ahmed; Shamsudin, Mariana Nor; Abdullah, Rasedee; Mohamed, Rahmah (Medwell Publishing, 2009)
Burkholderia pseudomallei is the causative agent of melioidosis, a serious disease of man and animals. The high mortality of B. pseudomallei infections may cause by lipopolysaccharides, an endotoxin. The biosynthesis of LPS is complex comprising three components, lipid A, core ohgosaccharide and O-specific antigen. In the current study, by using the available B. pseudomallei genome database provided by Wellcome. The study demonstrated that the bioinformatics comparative technique was able to annotate LPS genes in Burkholderia pseudomallei. By developing a simple and easy flow chart including the using of Artemis software, total of 44 putative ORFs involved in biosynthesis of lipopolysaccharide for B. pseudomallei and the genetic mapping for the ORFs have been successfully determined using bioinformatics and laboratory approach. It is about 95.7% of success for annotation based on the 46 genes that act as references. In near future, a suitable vaccine or antimicrobial may be developed by targeting the genes encoding the various components essential in LPS biosynthesis and survival of the pathogen.